Fryd og hverdag - Tybjerg, Tove (Religionsvidenskabeligt Tidsskrift, 1995)
In the article, the Danish historian of religion, Velhelm Grønbech, is compared and contrasted with his elder contemporary, the German sociologist of religion Max Weber. They both took a critical view of the developments of Western culture; they both emphasized the vital importance of religion to tthese developments, and they both took a hermeneutical approach to the study of religion. However, they were very different in their methodological attitudes. Unlike Grønbech, Weber devoted considerable effort to reflections on method, and this article is intended as an introduction to these reflections.